Potencial hídrico no xilema como ferramenta de manejo de irrigação do feijoeiro comum - Moraes, Luciana Corrêa (2019)
There are still few established parameters for the irrigation of annual crops using the water potential in xylem. The objective of this research was to determine the limit of the water potential of common bean, in which vegetative growth and productivity are not limited. Four experiments were implemented on July 4th, 2018 at the Capim Branco University Farm in Uberlândia, Brazil. BRS Cometa, BRS Style, BRS Madrepérola, BRSMG Majestoso and BRSMG Uai were cultivated, which are the factors evaluated in each experiment under a randomized complete block design. At 34 days after sowing, T1 experiment was induced to daily irrigation, T2 to an every-two-day irrigation, T3 to an every-four-day irrigation and T4 to an every-ten-day irrigation. These irrigations were maintained for the rest of the crop cycle. The water potential in xylem was monitored weekly in early morning (between 07:00 and 09:00) in one plant per plot throughout the trial. Pre-dawn water potential (between 04:00 and 06:00) was also checked on days 55 and 70 after sowing with the help of a Scholander pressure chamber. Plant height, stem diameter, plant mass, number of grains, number of total pods, mass of 100 grains, duration of the crop cycle and yield in grams per plant were also evaluated. Statistical level were performed through a 0.01 (1%) and 0.05 (5%) significance analysis by Tukey test. When irrigated every day the yield was 49% greater than the 10-day irrigation interval. Productivity begins decreasing when the potential is between -0.53 and -0.68 MPa.